Analisis Daya Saing dan Strategi Pengembangan Agribisnis Kopi Indonesia - andaro (SUAN PUBLISHER, 2026)
Sidikalang is one of Indonesia's most prominent coffee-producing regions with a long historical reputation for quality; however, it faces challenges in maintaining market position amidst global competition and inefficient supply chains. This study aims to analyze the competitiveness and formulate a sustainable development strategy for the coffee agribusiness in Sidikalang, Dairi Regency. The research employed a descriptive-comparative method using both quantitative and qualitative approaches. Data were collected from 60 coffee farmers through simple random sampling and 10 key stakeholders through purposive sampling. Competitiveness was measured using the Revealed Comparative Advantage (RCA) index, while the development strategy was formulated using the Internal-External (IE) Matrix and SWOT Analysis. The results indicate that Sidikalang coffee possesses a strong comparative advantage with an RCA score of 2.38, driven by its unique sensory profile and geographical indications. Bivariate analysis reveals that institutional strength and post-harvest technology significantly influence the added value at the farm level. The SWOT analysis positions the Sidikalang coffee agribusiness in Quadrant I (Aggressive Strategy), with a total weighted score of 3.05. The recommended strategy focuses on an